Statistical expertise in the Ecuadorian public administration: Emergence and legitimation mechanisms - Villacís, Byron (2021)
Statistics are an essential tool for governance in contemporary public administration. The advent of this discipline in Ecuador hinged on the role played by a field of experts that appeared and achieved legitimacy in the period running between 1927 and 2020. The present text asks about the role of internal and external factors as well as that of sociopolitical causes, in bringing about the development of statistics as a discipline in this country. The examination of historical archives and the completion of in-depth interviews discloses the fact that the advancement of the field of public statistics in Ecuador is the outcome   of the joint impact of four centripetal external forces and three centrifugal local factors.  The legacy of the Kemmerer mission, the influence of CEPAL, the growing automatization of Government and the international demand for adequate reporting, created powerful incentives for the growth of the profession.  These trends were reinforced by local government styles, frequent institutional redesign and recurrent redefinitions of organizational mandates. Initially, academia played an inconsistent and fragmented role in the production of expert statisticians. However, the increasing strength of government regulation and planning helped the profession to achieve institutional and disciplinary stability.  This text provides useful insights for efforts that attempt to show that statistics are not objective and isolated devices, but instead are the result of social relations that need to be approached from a historical perspective.